Deliberate premarket underpricing and aftermarket mispricing: new insights on IPO pricing - Reber, Beat; Vencappa, Dev (Elsevier, 2016)
We decompose initial returns into deliberate premarket underpricing and aftermarket mispricing using stochastic frontier analysis. We model deliberate underpricing as a function of proxies of information asymmetry surrounding IPO value between market participants. Equity retained is an unlikely signalling mechanism to convey IPO value to outside investors through deliberate premarket underpricing. The presence of lock-in agreements, underwriter fees, number of uses of proceeds, and venture capital or private equity backing have positive impacts on deliberate premarket underpricing. Demand for firms' capital also explains deliberate premarket underpricing, whereas new issues market conditions have no impact. All these factors are found to explain a significant fraction of the variations in our deliberate underpricing estimates. Deliberate underpricing is the more dominant component that makes up initial return when compared to the fraction of aftermarket mispricing. We attribute aftermarket mispricing to trading volume in IPO shares on the first day, price adjustment between the filing price range and the offer price, and offer size. Equity retained explains the aftermarket mispricing rather than the deliberate premarket underpricing in contradiction to the signalling argument. More reputable underwriters are likely to provide price support in the early aftermarket, whereas we observe no impact on deliberate premarket underpricing.